Three-dimensional mapping of seafloor using multibeam RESON SeaBat 8124 [compact disc] - 381096 Wong, Tze Xien (Skudai : Universiti Teknologi Malaysia, 2008)
Project Paper (Sarjana Muda Kejuruteraan (Geomatik) - Universiti Teknologi Malaysia, 2008